Tinjauan Konseptual Berwisata Berdasarkan Perspektif Al-Qur'an: Integrasi Ibadah dan Rekreasi - Nagga, Jumaedi; Asfar, Khaerul; Dja’fara, Syahril (Program Studi Ilmu Al-Quran dan Tafsir, 2025)
Tourism has become an important part of modern life, but moral issues often arise when such activities conflict with Islamic principles. This study seeks to analyze tourism from the perspective of the Qur’an, emphasizing its moral and spiritual aspects. Using the Qur’an as the primary reference supported by classical and contemporary interpretation as well as relevant hadith this research explores how tourism can be regarded as worship when carried out with good intentions and in accordance with Islamic ethics. The findings reveal several Qur’anic principles related to tourism. First, travel should be seen as a means of observing the signs of Allah’s power (QS al-‘Ankabut/29: 20; QS al-Rum/30: 9). Second, individuals must uphold social ethics and tolerance during their journeys (QS al-Hujurat/49: 13). Third, it is essential to preserve the environment (QS al-An‘am/6: 141). Relevant hadith on travel etiquette such as maintaining good character toward others also reinforce these principles. This study concludes that Qur’an-based tourism requires the integration of worship and recreation, focusing on learning, reflection, environmental care, and moral development. Therefore, tourism from an Islamic perspective is not merely recreation; it is an act that encompasses benefiting society, strengthening faith, and promoting moral values.